Amidst the COVID-19 pandemic childhood obesity is still an epidemic-spotlight on obesity's multifactorial determinants - Katya Saliba; Sarah Cuschieri (Health Sciences Review, 2021)
Purpose: Childhood obesity is a global epidemic and a chronic disease. Multifactorial determinants have long been linked with childhood obesity. These have been challenged with the onset of COVID-19 and the associated mitigation measures. The study aimed to re-highlight these determinants while exploring the effects of the ongoing COVID-19 pandemic on these pre-existing childhood obesity determinants, while providing evidence that may be beneficial for the post-COVID-19 recovery plan. Methods: A PubMed literature search (2016–2021) using the keywords, “childhood obesity”, “gender”, “sex”, “obesity in youth”, “obesity in adolescents”, “COVID-19″ and “SARS-CoV2” was performed. Results: Genetic predisposition, biologically low leptin levels, certain cultural beliefs and socio-economic statuses, as well as exposure to an “obesogenic” environment were found to have a positive association with childhood obesity. Additionally, the onset of COVID-19 further aggravates the childhood obesity epidemic, increasing childrens’ susceptibility to obesity and all associated consequential diseases. Discussion: A possible key to the control and prevention of the burden of childhood obesity, lies in dealing with its precursors and risk factors. Certain factors, including socio-cultural norms, cultural beliefs and geographical factors are amenable. COVID-19 further challenged these and it is evident that the childhood obesity epidemic is still a critical one. Encouraging preventative interventions, such as screening programs, public awareness and policies targeting the environment, amongst others, are recommended.